Chronic job burnout and daily functioning: a theoretical analysis - Bakker, A.; Costa, P. (Burnout Research, 2014)
In this article, we discuss the individual employee's role in the development of his/her job burnout. We review the antecedents and consequences of burnout, and propose a model with chronic burnout as a moderator of daily functioning in the workplace. Specifically, we argue that chronic burnout strengthens the loss cycle of daily job demands, daily exhaustion, and daily self-undermining. Additionally, we argue that chronic burnout weakens the gain cycle of daily job resources, daily work engagement, and daily job crafting. We conclude that employees with high levels of burnout need help in structurally changing their working conditions and health status.